Non-microbial methane emissions from tropical rainforest soils under different conditions. - Gaohui Jia (Public Library of Science (PLoS), 2021)
Non-microbial methane (NM-CH4), emissions from soil might play a significant role in carbon cycling and global climate change. However, the production mechanisms and emission potential of soil NM-CH4 from tropical rainforest remain highly uncertain. In order to explore the laws and characteristics of NM-CH4 emission from tropical rainforest soils. Incubation experiments at different environmental conditions (temperatures, soil water contents, hydrogen peroxide) and for soils with different soil organic carbon (SOC) contents were conducted to investigate the NM-CH4 emission characteristics and its influence factors of soils (0-10cm) that collected from a tropical rainforest in Hainan, China. Incubation results illustrated that soil NM-CH4 release showed a linear increase with the incubation time in the first 24 hours at 70 °C, whereas the logarithmic curve increase was found in 192 h incubation. Soil NM-CH4 emission rates under aerobic condition were significantly higher than that of under anaerobic condition at first 24 h incubation. The increasing of temperature, suitable soil water contents (0-100%), and hydrogen peroxide significantly promoted soil NM-CH4 emission rates at the first 24 h incubation. However, excessive soil water contents (200%) inhibited soil NM-CH4 emissions. According to the curve simulated from the NM-CH4 emission rates and incubation time at 70 °C of aerobic condition, soil would no longer release NM-CH4 after 229 h incubation. The NM-CH4 emissions were positively corelated with SOC contents, and the average soil NM-CH4 emission potential was about 6.91 ug per gram organic carbon in the tropical mountain rainforest. This study revealed that soils in the tropical rainforest could produce NM-CH4 under certain environment conditions and it supported production mechanisms of thermal degradation and reactive oxygen species oxidation. Those results could provide a basic data for understanding the soil NM-CH4 production mechanisms and its potential in the tropical rainforest.